(untitled) (Research, Society and Development, 2022)
The present study aimed to demonstrate low-cost alternatives for the teaching of Programming and Robotics in Elementary and High School institutions in order to seek alternatives to budget difficulties that public or private schools may have. It also sought to show possibilities to improve the quality of teaching through Programming and Robotics, as well as the impacts they may have when conducted in an interdisciplinary way with other disciplines, which can help mediate for a meaningful learning and for the construction process. of knowledge. For this, it carried out a literature review aiming to theoretically support the work, in addition to demonstrating concepts related to the presented theme. The conclusions obtained in the work can serve as a stimulus for the implementation of the teaching of Programming and Robotics in many schools, since there are cases in the literature of schools that, even with budgetary restrictions, were able to establish the theme in the school environment.